Islandness, sense of place, and the importance of 'story' in the islands of Newfoundland and Tasmania - Brinklow, L (ABC Hobart, 2010)
With Newfoundland, Canada, and Tasmania, Australia, coming into their own culturally in recent years - Newfoundland through its vibrant literary and musical scene, and Tasmania through literature, music, and visual art - the question arises: why do these two islands of similar sizes, populations, genealogies, and geographic placements, on opposite sides of the globe, have such vibrant cultures? Examining the issue through the lens of island studies, one could attribute it to the fierce sense of pride and independence that comes from living close to the elements in a bounded space, or from the specialness of being set apart from the mainland, or from the storytelling tradition, where islanders know that they must claim and reclaim their stories to ensure their accuracy. As Darwin has identified, islands are a laboratory for change. In this age of a global cookie-cutter culture, then, what do these two island cultures have to teach us about cultural diversity, originality, identity, and how cultures evolve? Through the lens of place and attachment to place - in this case, islands - and by looking at representations of Newfoundland and Tasmanian culture, this study will explore how attachment to place, island identity, and the prevalence of story play a significant role in islanders perceptions of self, individually and collectively.